Makna Yuridis Tindak Pidana Yang Sifatnya Ringan Dalam Konsep Judicial Pardon Ditinjau Berdasarkan Asas Legalitas - Nazara, Imanuel; Burhanudin, Krisna; Putra Frans, Mardian (Widya Yuridika, 2025)
The legal issue of this research is the blurring of the juridical meaning of light criminal acts in the provision of forgiveness by a judge or what is also called Judicial Pardon which is contained in Article 54 Paragraph (2) of Law Number 1 of 2023 concerning the Criminal Code. This research analyzes in particular the explanation of Article 54 Paragraph (2) relating to the phrase contained in that Article, namely minor criminal acts. Indicators of an act as a light criminal act are not explained explicitly, such as benchmarks for the lightness of the act, the threat of punishment, and the threat of a fine in the Criminal Code, thereby giving rise to ambiguity or unclear meaning which can cause inequality in the application of punishment in criminal law. in Indonesia. This research is normative legal research which examines it based on positive law. The results of this research are that regarding the meaning of minor criminal acts in the judge's giving of forgiveness is not in accordance with the principle of legality, namely that there is unclear meaning. The aim of this research is to explore the meaning of minor criminal acts in giving forgiveness by judges based on the principle of legality.